Descripción de una nueva subespecie de Tuza, Cratogeomys goldmani (Rodentia: Geomyidae), de San Luis Potosí, México - Alvarez, Ticul; Alvarez Castañeda, Sergio Ticul (Instituto de Ecología, A.C., 1996)
We reviewed seveml specirnens of Cratogeomys goldmani a gopher distribtited in central México. Spocimens from El Cedral, San luis Potosí differ from spccimens collected at ottier localities m several cranial chai acteristics and coloration to be recognized as a new subspecies. Por this reason, we named Ihe new supspecies doscribed boro as macuiatus because 97% of the reviewed specirnens have irregular wliite spots and snob charactenstic is not found arnong gophers of other .subspecies.